Virtuous nexus between corporate social performance and financial performance: a study of construction enterprises in China. (15th August 2016) - Xiong, Bo; Lu, Weisheng; Skitmore, Martin; Chau, K.W.; Ye, Meng
Abstract: Although business and society are thought in a vicious relationship for diminishing trust among stakeholders, a few studies indicate the existence of a reciprocal nexus between corporate social performance and corporate financial performance, known as the "virtuous cycle". Despite of some empirical studies in developed countries, little research has been conducted concerning the assumption in emerging markets, where large companies have more responsibilities to create positive and sustainable-shared values. This paper aims to explore the nexus between social performance and financial performance of Chinese companies for their global influential social and environmental impacts together with increasing awareness of corporate social responsibility (CSR). A two-step longitudinal design, including cross-lagged correlation analyses and longitudinal path analyses, is applied to examine the overall and decomposed links. It is found the virtuous cycle does exist in the overall and in most decomposed links within the context of large construction companies in China. These findings are beneficial for interested policy-makers, corporate managers, and the public to create shared value on CSR and therefore contribute to CSR improvements. Analysis results indicate a one-year time lag to be appropriate for examining the lead–lag relationship between corporate social performance and financial performance. The research also inspires a potential generalisation of the virtuous cycle by similarly examining it in other industries or other countries with diverse CSR contexts.